Promoting learners’ autonomy through listening log for teaching listening - Athena , Tera (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2019)
Learners need to motivate themselves to be an autonomy learner. They must be active to find many efforts to increase their skill. In listening class, the lecturers need to stimulate the students’ ability in listening skill by applying a sequence questions in form of Listening Log. From the listening Log, it can be illustrated the students effort to listen many listening passage from many sources and places. They do not only study by depend on the teaching and learning in a classroom. Based on the listening log, it can be seen that most of the students were aware about their responsible toward listening skill.